2022
DOI: 10.3390/app12052622
|View full text |Cite
|
Sign up to set email alerts
|

Reliability Analysis of Military Vehicles Based on Censored Failures Data

Abstract: The paper proposes a methodology of reliability testing as applied to vehicles used in military transport systems. After estimating the value of the reliability function using the Kaplan–Meier estimator, reliability models were developed and analysed. The neural model, which achieved the value of the correlation coefficient R exceeding 0.99, was determined to fit the empirical data the best. On the basis of the approximated reliability function of several models, the reliability characteristics of the tested s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 63 publications
0
11
0
1
Order By: Relevance
“…A fuzzy model with a similar accuracy reflected the values of an empirical reliability function. In turn, in [34], the multilayer perceptron (MLP) neural model was slightly better at approximating the light utility vehicle reliability function relative to the exponential and Weibull distributions. Whereas, in the case of fluid filling equipment in the automotive manufacturing industry, Soltanali et al [45] demonstrated a significant improvement in the accuracy of reliability predictions using the Adaptive Neuro-Fuzzy Inference System model, compared to Weibull and Non-Homogeneous Poisson Process models.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…A fuzzy model with a similar accuracy reflected the values of an empirical reliability function. In turn, in [34], the multilayer perceptron (MLP) neural model was slightly better at approximating the light utility vehicle reliability function relative to the exponential and Weibull distributions. Whereas, in the case of fluid filling equipment in the automotive manufacturing industry, Soltanali et al [45] demonstrated a significant improvement in the accuracy of reliability predictions using the Adaptive Neuro-Fuzzy Inference System model, compared to Weibull and Non-Homogeneous Poisson Process models.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Statistical methods Generalized Gamma distribution Cabin door lock on rail vehicles [43] Reliability series structure model Aircraft commutators [53] Statistical methods and fuzzy logic Weibull and fuzzy models Light combat aircraft [60] Statistical methods and neural networks Exponential, Weibull and MLP models Light utility vehicles [34] Weibull, Non-Homogeneous Poisson Process and Adaptive Neuro-Fuzzy Inference System models Fluid filling equipment in automotive manufacturing industry [45] Neural networks Neural models (MLP) Vehicles [25] Neural model of reliability allocation Machine tools [11] Neural networks and partial swarm optimization Hybrid model Industrial robot systems [2] Ordered weighted averaging aggregation operator Reliability allocation model Thin-film transistor liquid-crystal display [7] Probabilistic methods Reliability models including hard and soft failures Micro-electro-mechanical systems devices [46][37]…”
Section: Models Case Study Papermentioning
confidence: 99%
See 2 more Smart Citations
“…The fleet of reliable vehicles is one of the main factors determining the high quality and timely implementation of processes in modern transport systems. The condition for the effective operation of the system is to maintain the means of transport in a state of technical efficiency and be ready to perform tasks [1,2]. The fulfilment of this condition is possible thanks to the organization of operating systems with appropriate technical resources to carry out processes of diagnosis, servicing and repair of vehicles.…”
Section: Introductionmentioning
confidence: 99%